Desarrollo de una metodología de evaluación de caminos vecinales para la conservación vial (MOPT) - Watson-López, Marcela (Instituto Tecnológico de Costa Rica, 2009)
The deteriorating conditions in the cantonal road network, lack of financial resources, trained personnel, lack of awareness of communities and the mistaken policy of delaying intervention activities to improve road conditions, has led to have a inefficient management of roads. Despite this, it has tried to gradually implement an adequate road management, so it is given due importance to road maintenance, but no results have been completely satisfactory. Given this situation arises to develop a methodology for evaluating roads for road maintenance, so that may help solve this problem and thus have a tool for estimating the condition or status of the road being evaluated, so are chosen correctly the maintenance activities necessary to have roads in good condition. To accomplish this objective, it was necessary to develop a questionnaire to be applied to five municipalities, conduct a needs inventory to identify potential problems and maintenance activities to improve the condition of the roads and consult appropriate literature, so that allow to develop a simple and useful to the agencies responsible for the roads can be implemented. As a main conclusion is determined that the use of the proposed methodology allows for a portion of the current state of the road, valuable information that helps to develop a useful database and 2projections to determine the time that is necessary to implement conservation activities.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Construcción, 2009.
Keywords: Carreteras; Mantenimiento; Construcción; Desgaste; Alcantarillas